A review of the bioeffects of low-intensity focused ultrasound and the benefits of a cellular approach - Collins, Morgan N.; Mesce, Karen A. (Frontiers in Physiology, 2022)
This review article highlights the historical developments and current state of knowledge of an important neuromodulation technology: low-intensity focused ultrasound (FUS). Because compelling studies have shown that FUS can modulate neuronal activity non-invasively, especially in deep brain structures with high spatial specificity, there has been a renewed interest in attempting to understand the specific bioeffects of FUS at the cellular level. Such information is needed to facilitate the safe and effective use of FUS to treat a number of brain and nervous system disorders in humans. Unfortunately, to date, there appears to be no singular biological mechanism to account for the actions of FUS, and it is becoming increasingly clear that different types of nerve cells will respond to FUS differentially based on the complement of their ion channels, other membrane biophysical properties, and arrangement of synaptic connections. Furthermore, neurons are apparently not equally susceptible to the mechanical, thermal and cavitation-related consequences of FUS application—to complicate matters further, many studies often use distinctly different FUS stimulus parameters to achieve a reliable response in neural activity. In this review, we consider the benefits of studying more experimentally tractable invertebrate preparations, with an emphasis on the medicinal leech, where neurons can be studied as unique individual cells and be synaptically isolated from the indirect effects of FUS stimulation on mechanosensitive afferents. In the leech, we have concluded that heat is the primary effector of FUS neuromodulation, especially on motoneuons. We discuss that the mechanical bioeffects of FUS, which are frequently described in the literature, are less reliably achieved as compared to thermal ones, and that observations ascribed to mechanical responses may be confounded by activation of synaptically-coupled sensory structures or artifacts associated with electrode resonance. Ultimately, both the mechanical and thermal components of FUS have significant potential to contribute to the sculpting of specific neural outcomes. Because FUS can generate significant modulation at a temperature < 5°C, which is believed to be safe for moderate durations, we support the idea that FUS should be considered as a thermal neuromodulation technology for clinical use, especially targeting neural pathways in the peripheral nervous system.